Evaluation of Attitudes on Dating Violence (EADV): A New Brazilian Instrument - Gregori, Amanda Gomes (2022)
Lack of assessment tools for the Brazilian population is a challenge regarding dating violence. Aim of this study was to analyze psychometric properties of the instrument Evaluation of attitudes on dating violence (EADV). Sample comprised 1,027 university students from five Brazilian regions with a mean age of 22.5 years (SD = 3.7) who answered 39 items. An Exploratory Graph Analysis (EGA) was used with 513 participants establishing three dimensions with good internal consistency (Psychological and Physical Violence (A = 0.85), Empathy (A = 0.78), Stalking (A = 0.87)). A confirmatory factorial analysis with 514 participants showed adequate results. Results show the scale reliability and adequacy to its use with the Brazilian population on research and intervention.